Interleukin-34 in the Serum and Synovial Fluid of Rheumatoid Arthritis Patients: Relation to Disease Activity and Radiographic Damage - Selim, Zahraa I.; Rashad, Sonya M.; Abdelaziz, Marwa Mahmoud; Salah, Shaimaa; Fouad, Doaa Mohammad; Hetta, Helal F. (Aktuelle Rheumatologie, 2019)
Background Interleukin 34 (IL-34) is a recently discovered proinflammatory cytokine that can promote inflammation and osteoclastogenesis in arthritic joints. In this study, we tried to assess the serum and synovial fluid (SF) levels of IL-34 in rheumatoid arthritis (RA) patients, and to determine its relationship with disease activity and radiographic damage.Patients and methods ELISA was used to evaluate IL-34 levels in the serum of RA patients (n=50), osteoarthritis (OA) patients (n=28), and healthy control subjects (n=20) and in SF isolated from RA and OA patients. Disease activity in RA patients was assessed using the disease activity score-28 (DAS 28). The extent of radiographic joint damage, narrowing, and erosions was assessed.Results Serum IL-34 level was significantly elevated in RA patients compared to that in OA patients and healthy controls (P<0.0001). Synovial IL-34 level was also significantly elevated in RA patients compared to that in OA patients (P=0.0004). Serum and synovial IL-34 levels were significantly higher in cases that were rheumatoid factor (RF) positive (n=28) compared to the levels in RF-negative RA cases (n=22) (P=0.03 and P=0.04, respectively). Serum and synovial IL-34 levels were positively correlated with RF (r=0.43, P=0.02 and r=0.39, P=0.03, respectively), and with the extent of radiological damage (SENS) (P=0.0002 and P<0.0001, respectively). However, no significant correlation between IL-34 levels and disease activity was found.Conclusion IL-34 appears to play a key role in the pathogenesis of RA and contribute to bone destruction, making it a potential therapeutic target in the management armamentarium of the disease.
Keywords: Interleukin-34; Rheumatoid arthritis; DAS-28; radiographic damage